STRATEGIC MANAGEMENT BASED ON TRI HITA KARANA A BALINESE LOCAL WISDOM APPROACH TO EDUCATIONAL INSTITUTION DEVELOPMENT - Edwin, Edwin; Josiharu Edmund Franky (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2026)
This research seeks to examine the applicability of the Balinese philosophy Tri Hita Karana (THK) which embodies the principles of harmony with God (parahyangan), humanity (pawongan), and nature (palemahan), as a conceptual foundation for developing strategic management in education. It addresses typical challenges such as misalignment between institutional strategies and core values, ineffective stakeholder engagement, and the lack of sustainability in school governance. This investigation relied on a qualitative synthesis of existing literature, encompassing journal publications, authoritative texts, and policy documents that discuss strategic management, leadership, and the principles of THK. A thematic content analysis was conducted to trace the conceptual interconnections between THK principles and strategic management practices. Results indicate that THK acts as a unifying foundation, bringing together spiritual, social, and ecological principles in the formulation of institutional strategies. Such integration encourages ethical leadership, inclusiveness in governance, and continuity in organizational sustainability. The study argues that THK extends beyond its traditional context, forming a strategic approach that reinforces institutional ethics and adaptability. Furthermore, this research contributes to the development of a contextually grounded theory of educational strategic management and calls for empirical validation through future field-based investigations.